Stroke due to atrial fibrillation in a population‐based stroke registry (Ludwigshafen Stroke Study) CHADS2, CHA2DS2‐VASc score, underuse of oral anticoagulation, and implications for preventive measures. Issue 1 (12th July 2012) - Palm, F.; Kleemann, T.; Dos Santos, M.; Urbanek, C.; Buggle, F.; Safer, A.; Hennerici, M. G.; Becher, H.; Zahn, R.; Grau, A. J.
<x xml:space="preserve">Abstract</x> Background and purpose Atrial fibrillation (AF) is amongst the most important etiologies of ischaemic stroke. In a population‐based stroke registry, we tested the hypothesis of low adherence to current guidelines as a main cause of high rates of AF‐associated stroke. Methods Within the Ludwigshafen Stroke Study (LuSSt), a prospective ongoing population‐based stroke register, we analyzed all patients with a first‐ever ischaemic stroke (FEIS) owing to AF in 2006 and 2007. We determined whether AF was diagnosed before stroke and assessed pre‐stroke CHADS2 and CHA2DS2‐VASc scores. Results In total, 187 of 626 patients with FEIS suffered from cardioembolic stroke owing to AF, which was newly diagnosed in 57 (31%) patients. Retrospective pre‐stroke risk stratification according to CHADS2 score indicated low/intermediate risk in 34 patients (18%) and high risk (CHADS2 ≥ 2) in 153 patients (82%). Application of CHA2DS2‐VASc score reduced number of patients at low/intermediate risk (CHA2DS2‐VASc score 0–1) to five patients (2.7%). In patients with a CHADS2 score ≥ 2 and known AF (n = 106) before stroke, 38 (36%) were on treatment with vitamin K antagonists on admission whilst only in 16 patients (15%) treatment was in therapeutic range. Conclusions Our study strongly supports the hypothesis that underuse of oral anticoagulants in high‐risk patients importantly contributes to AF‐associated stroke. CHA2DS2‐VASc score appears to be a more valuable risk stratification tool than CHADS2 score. Preventive measures should focus on optimizing pre‐stroke detection of AF and better implementation of present AF‐guidelines with respect to anticoagulation therapy.